AB0603 Why Leg Ulcers do not Heal? A Prospective Study Showing High Proportion of Small Vessel Vasculitis. (10th June 2014) - Ravindran, V.; Rajendran, S.; Vijayan, R.
Abstract : Background: Non healing cutaneous ulcers of lower limbs can have several different aetiologies. [1] It is likely that the patients with such ulcers would be treated with empirical therapies and may also undergo (unnecessary) venous procedures. Small vessel vasculitides (leucocytoclastic or non leucocytoclastic) are one of the important causes of non healing cutaneous leg ulcers. [2] Objectives: The primary objective of this prospective study was to ascertain the cause of non healing cuatneous ulcers of the lower limbs. Methods: Between May 2010 and April 2013 (3years) consecutive adult patients (age 18 to 75 years) who had one or more persistent leg ulcers (with or without a history of recurrent ulcerations in legs) for more than 2 years presenting to either departments were prospectively enrolled. Relevant details were extracted using a predefined proforma and included: demographic details, drug history, comorbidities, clinical features, investigations including ANCA, complement levels, cryoglobuilins, HIV and Hepatitis viral serology etc. and venous and arterial Dopplers, microscopy and culture of the ulcer swab in cases of infected looking ulcers. Biopsies were obtained from the ulcer edges and nonulcerated sites where skin lesions were also present. In cases of ulcers deemed to be a manifestation of a primary systemic vasculitis based on the EMEA classification, BVAS was used to assess disease activity. Results: A total of 51 patients were assessed. Mean age was 53±10.3 years and 39 (76%) were male. Eight (16%) patients were diabetic. History of some type of venous surgery was present in 30 (59%) and 9 had such procedures more than once. Biopsy confirmed small vessel vasculitis of various types in a majority (76%) of patients (table 1 ). Drug induced cutaneous vasculitis was not present in this cohort. Table 2 shows that in 9 (18%) patients the leg ulcers were one of the manifestations of a primary systemic vasculitis i.e GPA, EGPA, MPA or PAN. Leg ulcers in these patients ran an indolent course with a variety of low to moderate grade of activity features reflected also in the BVAS range of 9 to 15. All patients with small vessel vasculitis were treated with immunosuppressive therapy including glucocorticoids with good effect [complete healing of ulcer(s) in 21 patients with no relapse in 24 weeks follow up period]. Conclusions: In this cohort of patients with chronic non healing leg ulcers systematic assessment revealed small vessel vasculitis as the leading cause thus enabling specific measures of treatment being instituted. References: Mekess JR et al. Causes, investigation and treatment of leg ulceration. British Journal of Dermatology 2003; 148: 388–401 Gonzalez-Gay MA et. Other vasculitides including small-vessel vasculitis. In: Oxford Textbook of Rheumatology 3rd ed, Isenberg DA et al (eds). OUP 2004, pp983-988. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1648